Problems of personality in their philosophical setting - Ramos, Paz Gomez
The purpose of the researcher is to have a better understanding of the problems of personlity and adjustment from the philosophical point of view. With this type of understanding, she hopes to be able to give more appropriate suggestions for application. The researcher listed various forms of personalism: pantheistic, absolute, pluralistic or finistic, aetheistic, relative, theological or purely finsitic, and typical personalism.
Keywords: Personality -- Philosophy